Novel Hemizygous Mutations of TEX11 Cause Meiotic Arrest and Non-obstructive Azoospermia in Chinese Han Population - Ji, Zhiyong; Yao, Chencheng; Yang, Chao; Huang, Chuan; Zhao, Liangyu; Han, Xia; Zhu, Zijue; Zhi, Erlei; Liu, Nachuan; Zhou, Zhi; Li, Zheng (Frontiers in Genetics, 2021)
Testis-expressed gene 11 (TEX11) mutation has been associated with non-obstructive azoospermia (NOA) and meiotic arrest. An analogous mutation of TEX11 in the mouse impairs meiosis and can be rescued by in vitro expansion of SSCs and gene therapy. However, a lack of genetic screening of a large cohort of Asian patients (including pedigree analysis) and proper functional evaluation limits the clinical application of TEX11 mutation screening. Thus, we performed whole-exome sequencing (WES) in 479 patients with NOA and identified three novel mutations (two splicing mutations and one missense mutation) in TEX11 in 3 pairs of siblings from three families and 4 novel pathogenic mutations (three frameshift mutations and a nonsense mutation) of TEX11 in 4 sporadic NOA-affected cases. Novel variants among family members were segregated by disease phenotype and all the 7 mutations were predicted to be pathogenic. Histological analysis showed that 3 patients with TEX11 mutations underwent meiotic arrest and the 4 mutations resulting in protein truncations and defective meiosis-specific sporulation domain SPO22 were validated by Western blot. In total, we find 7 of 479 patients of NOA (1.5%) carrying TEX11 mutations. Our study expands the knowledge of mutations of TEX11 gene in Asian patients with NOA. The high prevalence and X-linked inherited mode indicated that TEX11 might be included in genetic screening panels for the clinical evaluation of patients with NOA.